Analisis Kepuasan Pelayanan Pasien COVID-19 di Rumah Sakit Santo Antonio Baturaja - Lukman Hakim; Chairil Zaman; Arie Wahyudi (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Health systems around the world are facing challenges in the form of the increased demand for health care by people with COVID-19. Unprecedented circumstances such as the recent COVID-19 pandemic are putting immense pressure on healthcare providers. service quality must be considered and always focus on customer satisfaction. The purpose of this study was to look at the factors related to patient satisfaction. This study uses a quantitative method with a Cross Sectional approach. Statistical test using Chi Square test. Multivariate analysis in this study used multiple logistic regression analysis. In this study, it can be concluded that there is a relationship between age (p = 0.021; OR = 12,000, tangibles (p = 0.009; OR = 8.381), reliability (p = 0.041; OR = 4.571), responsiveness (p = 0.006; OR = 8.708), empathy (p= 0.002; OR=12,667) and assurance with service satisfaction for Covid 19 patients at Santo Antonio Baturaja Hospital, OKU Regency in 2021 (p= 0.001; OR=16,714) There is no sex relationship (p= 0.933), education ( p = 0.654), and occupation (p = 1,000). The most dominant variable is age (p = 0.025; OR = 202.606). Suggestions for the antonio hospital in particular, the findings of this study can be used by referral hospitals for inpatients of covid patients, so that pay attention to the age of the respondent in order to provide extra services to elderly patients.